Biventricular Repair in Heterotaxy Patients. (April 2015) - Makhija, Zeena; Marwah, Ashutosh; Mishra, Smita; Kumar, Jay; Goel, Apoorva; Sharma, Rajesh
Background: Heterotaxy patients' hearts may or may not be suitable for biventricular repair depending on anatomy. Even in the subset that are amenable to surgical septation, cardiac anatomy may present multiple difficulties in achieving a satisfactory repair. However, it is also well known that heterotaxy patients are not ideal candidates for univentricular repair. Methods: From 2007 until 2012, a total of 20 patients (11 male) with heterotaxy syndrome underwent biventricular repair (left atrial isomerism: 10 and right atrial isomerism: 10) in our center. Their median age at surgery was 40 (range: 3-108) months. Ten patients had dextrocardia. Eleven patients presented with bilateral superior vena cava, three with inferior vena cava (IVC) draining into left atrium, and six with IVC interruption with azygos or hemiazygos continuation. Anomalous pulmonary venous drainage was present in eight patients. One had a common atrium. Atrioventricular septal defect (AVSD) occurred in nine (complete AVSD in seven) patients. Eight patients had double outlet right ventricle (DORV), one hadd -transposition of great arteries (d -TGA), and two had congenitally corrected transposition of the great arteries (CC-TGA). Prior palliative procedures included pulmonary artery banding in three patients and left modified Blalock-Taussig shunt in one patient. Complex intra-atrial baffle constructions were required in all patients to direct pulmonary and systemic venous inflow to the appropriate ventricle. Complete AVSDs were corrected using two-patch technique. Intraventricular tunnel repair was done for DORV. Combined atrial and arterial switch was required to rectify abnormal connections in a child with congenitally corrected transposition with normal pulmonary valve, while a Rastelli + Senning was needed in two children with CC-TGA with pulmonary atresia (n = 1) and double outlet of the right ventricle (n = 1). Results: Major early postoperative complications included intestinal gangrene in four patients for which they underwent bowel resection. Two of these patients could not be salvaged. One patient required coiling of aortopulmonary collateral for early postoperative pulmonary hemorrhage. Two patients needed a tracheostomy for prolonged mechanical ventilatory support. Five patients had a pacemaker implanted for complete heart block. There were no instances of atrial baffle stenosis. Median follow-up was 27 (range: 2-46) months. There was one late death secondary to pneumonia. Conclusions: Satisfactory survival outcomes can be achieved in heterotaxy patients who undergo hemodynamically acceptable biventricular repair. Borderline ventricular hypoplasia and trivial atrioventricular valve regurgitation should not be considered as discouraging factors in anatomically suitable heterotaxy patients as it is possible to adopt a two-stage repair in such patients to achieve biventricular repair at a later stage. Anticipating a higher incidence of conduction problems and gut malrotation preemptively can help reduce the morbidity.